Antihypertensive Properties of a Pea Protein Hydrolysate during Short‐ and Long‐Term Oral Administration to Spontaneously Hypertensive Rats. Issue 5 (1st April 2016) - Girgih, Abraham T.; Nwachukwu, Ifeanyi D.; Onuh, John O.; Malomo, Sunday A.; Aluko, Rotimi E.
Abstract: This study investigated short‐term (24 h) and long‐term (5 wk) systolic blood pressure (SBP)‐lowering effects in spontaneously hypertensive rats (SHR) of a 5 kDa membrane pea protein hydrolysate permeate (PPH‐5) produced through thermoase hydrolysis of pea protein isolate (PPI). Amino acid analysis showed that the PPH‐5 had lower contents of sulfur‐containing amino acids than the PPI. Size‐exclusion chromatography indicated mainly low molecular weight (<10 kDa) peptides in PPH‐5 but not in the PPI. The PPH‐5 had renin and angiotensin converting enzyme inhibition IC50 values of 0.57 and 0.10 mg/mL ( P < 0.05), respectively, and consisted mainly of peptides with 2 to 6 amino acids. Mass spectrometry analysis revealed mainly hydrophilic tetrapeptide sequences. After a single oral administration (100 mg/kg body weight) to SHR, the unheated PPI showed weakest ( P < 0.05) SBP‐lowering effect with a –4 mm Hg maximum when compared to –25 mm Hg for heat‐treated PPI and –36 mm Hg for PPH‐5. Incorporation of the PPH‐5 as 0.5% or 1% (w/w) casein substitute in the SHR diet produced maximum SBP reductions of –22 or –26 mm Hg ( P < 0.05), respectively after 3 wk. In comparison, the unhydrolyzed PPI produced a maximum SBP reduction of –17 mm Hg also after 3 wk. Potency of the pea products decreased in the 4th and 5th wk, though SBP values of the treated rats were still lower than the untreated control. We conclude that the antihypertensive potency of PPH‐5 may have been due to the presence of easily absorbed hydrophilic peptides.